PENYELESAIAN SENGKETA MEREK PURE KIDS DENGAN MEREK PURE BABY - Suharta, Daniel (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Registration of a trademark serves to distinguish goods and services produced by one company from another. By registering a trademark, entrepreneurs get a legal protection. The function of registering a trademark is to avoid imitation by other parties. Even though it has been registered, there are still many trademark disputes that occur. The problems discussed in this thesis are how to protect brands in Indonesia, how to resolve brand disputes such as the case between the Pure Kids brand and the Pure Baby brand. The method used in writing this thesis is normative legal research (juridical normative), namely legal research that refers to legal norms contained in laws and regulations, books, legal journals, and electronic/internet media. Registered marks have legal protection for 10 years in accordance with Article 35 paragraph (1) of Law Number 20 of 2016. Marks that have been registered with the Director General of Intellectual Property Rights that are proven to be plagiarizing or imitating previous marks are subject to sanctions for deletion and cancellation of trademark registration in accordance with Articles 76 to with Article 79 of Law Number 20 of 2016. Article 21 paragraph (1) of Law Number 20 of 2016 provides an understanding of the similarity of marks in essence, is the resemblance caused by the existence of a dominant element between one Mark and another, so that it creates the impression there are similarities in terms of form, between elements, as well as similarities in the sound of speech contained in the brand. Settlement of trademark disputes can be carried out in two ways, namely, by filing a lawsuit to the Commercial Court (Article 83 of Law Number 20 of 2016) and resolving disputes through arbitration or alternative dispute resolution. In accordance with the dispute case between the Pure Kids Brand and the Pure Baby Brand, the dispute resolution is carried out by filing a lawsuit to the Commercial Court. After being examined by the Panel of Judges, there are similarities in essence, namely, the similarity of the sound of pronunciation, the similarity of the types of goods sold and traded